THERMAL PROCESSING OF AGARICUS BISPORUS AND ITS CONTROL VARIABLES - Salas de la Torre, N. (2003)
The main objective of this work to estab1ish the controlled use of heat as a function of the pH in order to destroy all the microorganisms that are this bacterias anaerobic forced thermopiles and essentially mesófilas. The bacteria more resistant esporulada to 1he heat is Clostridium botulinum and it is considered lndicative microorganísm of the sterellization. Another parameter of very important control is the quality of the matter it prevails that it can resist the operations of thermal prcsecution, the classification is made in function to the hat size, weight, color and it forms.